2020
DOI: 10.1007/s42770-020-00285-2
|View full text |Cite
|
Sign up to set email alerts
|

The correlation analyses of bacterial community composition and spatial factors between freshwater and sediment in Poyang Lake wetland by using artificial neural network (ANN) modeling

Abstract: As one of the most important components of the lake ecosystem, microorganisms from the freshwater and sediment play an important role in many ecological processes. However, the difference and correlation of bacterial community between these two niches were not clear. This study investigated the diversity of microbial community of freshwater and sediment samples from fifteen locations in Poyang Lake wetland. The correlation between the bacterial community and physicochemical property of Poyang Lake wetland was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 56 publications
2
8
0
Order By: Relevance
“…In the vertical distribution of the water column, the OTUs, richness, and diversity of bacteria in eutrophic reservoirs were also significantly higher than those in oligotrophic reservoirs and were significantly correlated with variables related to the nutritional status. Recent studies have shown that the nutritional status might be an important driving force for increased bacterial community diversity (Li et al, 2017;Sun et al, 2020). In our study, bacterial OTUs, richness, and diversity of the hypolimnion were found to be significantly greater than those of the epilimnion and thermocline in the same reservoir.…”
Section: Thermal Stratification and Nutrients Might Play Key Roles In Shaping The Vertical Dynamic Distribution Of The Bacterial Communitsupporting
confidence: 47%
“…In the vertical distribution of the water column, the OTUs, richness, and diversity of bacteria in eutrophic reservoirs were also significantly higher than those in oligotrophic reservoirs and were significantly correlated with variables related to the nutritional status. Recent studies have shown that the nutritional status might be an important driving force for increased bacterial community diversity (Li et al, 2017;Sun et al, 2020). In our study, bacterial OTUs, richness, and diversity of the hypolimnion were found to be significantly greater than those of the epilimnion and thermocline in the same reservoir.…”
Section: Thermal Stratification and Nutrients Might Play Key Roles In Shaping The Vertical Dynamic Distribution Of The Bacterial Communitsupporting
confidence: 47%
“…Other bacterial phyla declined over the period of accelerated eutrophication, such as Nitrospirae which dropped in relative abundance between 1970 and 1990 when nutrient concentrations were highest. Previous studies have also found that the relative abundance of Nitrospirae declined with increasing phosphorus (Liu et al, 2020; Xiong et al, 2012) and NH 4 ‐N concentrations (Sun et al, 2020). Chloroflexi were relatively abundant from the 1900s but consistently declined over time.…”
Section: Discussionmentioning
confidence: 87%
“…Urban color, in the general sense, can be regarded as the collection of color attributes of all visual objects in the urban spatial environment. It includes the color attributes of buildings and structures in the city, the colors of natural mountains and geography as the background of the urban spatial domain, and even the people and vehicles moving in the urban spatial entity [21].…”
Section: Color Element Data Analysis Model Construction For Urban Spa...mentioning
confidence: 99%
“…Urban color, in the general sense, can be regarded as the collection of color attributes of all visual objects in the urban spatial environment. It includes the color attributes of buildings and structures in the city, the colors of natural mountains and geography as the background of the urban spatial domain, and even the people and vehicles moving in the urban spatial entity [ 21 ]. From the perspective of color creation and planning design of the urban spatial environment, we often divide the color information covered in the urban spatial environment into fixed color information attributes, semifixed color information attributes, and mobile color information attributes.…”
Section: Color Element Data Analysis Model Construction For Urban Spa...mentioning
confidence: 99%